Validity and reliability of the Indonesian version of tinnitus handycap inventory (Faculty of Medicine Universitas Indonesia, 2015)
Background: To translate and assess the validity and reliability of the Indonesian version of Tinnitus Handycap Inventory (THI) as an psychometric instrument for evaluating the quality of life in tinnitus patients. This instrument will support the clinicians to determine the appropriate tinnitus management for them. Methods: A cross-sectional psychometric validation study was performed to assess the internal consistency, reliability and validity of the Indonesian version of THI in 50 subjective tinnitus patients at ENT outpatient clinic of Cipto Mangunkusumo Hospital between May-August 2010. 25 question items of original THI were translated, back-translated and validated using the transcultural validation by WHO. Results: The validity test demonstrated a significant correlation in the emotional and the catastrophic scale whilst there was no significant correlation in the functional scale for item F2 and particularly for item F15. Nevertheless, the validity test on the functional scale showed a good result. This study also showed high internal consistency and reliability for the total scale (Cronbach-α = 0.91) Conclusion: The evaluation result indicated that the reliability of adapted Indonesian version of the THI in our study is relatively high and could be applied in clinical examination or further otolaryngology study by both specialists and general physicians.